Penggunaan matlab simulink dalam pengajaran dan pembelajaran penukar kuasa mod pensuisan (PKMP) untuk pelajar pra - siswazah - Yushaizad Yusof,; Nasrudin Abd. Rahim, (Penerbit Universiti Kebangsaan Malaysia, 2010)
Power electronics has become a departmental basic course for undergraduate students of electrical and electronics engineering program at UKM. To help students understand this course easily, quickly and efficiently; teaching and learning process based on computer modeling and simulation are introduced. This approach is an alternative to laboratory experiment which is costly. This paper discusses implementation of Matlab Simulink software in modeling a Buck converter. Students are exposed on how to construct a circuit model, to analyze switching operation, and control system before Buck converter simulation is being executed. Results from the computer simulation should verifiy the theory that has been discussed in class. Hence, this paper can be a basic guideline for computer modeling and simulation-based laboratory experiment for power electronics course